Peningkatan Kesadaran Masyarakat terhadap Penggunaan Produk Tabungan Syariah - Jusman Jusman; Reni Delfira; Nur An’nisa. R; Anita Lestari Putri (Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze the level of public awareness regarding the use of Islamic savings products and to identify the factors influencing public interest in Islamic banking services. This research employs a descriptive method with a qualitative approach based on literature review and interviews. Data were analyzed using qualitative descriptive techniques through reduction, interpretation, and theoretical synthesis. The results indicate that public awareness remains at a low to moderate level. Most people only understand the basic concept of Islamic banking without comprehending contracts, profit-sharing systems, and fundamental differences from conventional banking. This condition is influenced by low Islamic financial literacy, ineffective socialization, limited access to information, and social environmental factors. Educational efforts have improved knowledge but have not significantly changed behavior. Therefore, a comprehensive strategy is needed through literacy strengthening, digital media optimization, and community leader involvement.